An Ultrasound Robotic System Using the Commercial Robot UR5 - Mathiassen, Kim; Fjellin, Jørgen Enger; Glette, Kyrre; Hol, Per Kristian; Elle, Ole Jakob (Frontiers in Robotics and AI, 2016)
The use of robots in health care has increased dramatically over the last decade. One area of research has been to use robots to conduct ultrasound examinations, either controlled by a physician or autonomously. This paper examines the possibility of using the commercial robot UR5 from Universal Robots to make a tele-operated robotic ultrasound system. Physicians diagnosing patients using ultrasound probes are prone to repetitive strain injuries, as they are required to hold the probe in uncomfortable positions and exert significant static force. The main application for the system is to relieve the physician of this strain by letting the them control a robot that holds the probe. A set of requirements for the system is derived from the state-of-the-art systems found in the research literature. The system is developed through a low-level interface for the robot, effectively building a new software framework for controlling it. Compliance force control and forward flow haptic control of the robot was implemented. Experiments are conducted to quantify the performance of the two control schemes. The force control is estimated to have a bandwidth of 16.6 Hz, while the haptic control is estimated to have a bandwidth of 65.4 Hz for the position control of the slave and 13.4 Hz for the force control of the master. Overall, the system meets the derived requirements and the main conclusion is that it is feasible to use the UR5 robot for robotic ultrasound applications.